USTED y SU CRÉDITO: Reportes de Crédito - Joan P. Elmore; Michael S. Gutter; Travis P. Mountain (EDIS)
This is part of the Spanish-language version of the You and Your Credit series. Written by Joan P. Elmore, Michael S. Gutter, and Travis P. Mountain, and published by the UF Department of Family, Youth and Community Sciences, February 2012.